Fuzzy-Pid Controller Design for Uav Hybrid Energy Propelled with Differential Box - San Juan-Urrutia, E; Canete-Arratia, L; Adasme-Soto, P; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2021)
This work provides the design of fuzzy-PID controller for energy management over a hybrid propulsion system in unmanned aerial vehicle. The simulation model of propulsion system and propeller dynamics have been developed by MATLAB-Simulink environment and his Simscape library. The main controller is composing for three controllers: Electric motor controller, an engine controller and energy manager. The last deliver set point to individual controllers. All PID controllers have been tuned by root locus methodology. Performance results was made into a specific flight scenario. All controllers have performed good results, showing a correct use of energy sources into the unmanned aerial vehicle unmanned. © 2021 IEEE.